Strategi Badan Narkotika Nasional Dalam Penanganan Narkoba Di Kota Palu - Bahar, Anisa; Mufti, Muhammad Irfan; Afandi, Muhammad (JPS: Journal of Publicness Studies, 2024)
Drug abuse has become one of the most troubling phenomena, especially in the community, to help the government overcome the problem of drug dangers, and the increasingly uncontrolled illicit circulation of narcotics has made the National Narcotics Agency (BNN) form the National Narcotics Agency in Palu City. The purpose of this study is to find out how the management strategy in handling drugs at the national narcotics agency kora palu. The method used in this study is qualitative descriptive method. By using kooten theory in salusu (2006) yairu organizational strategy (corporate strategy), program strategy (program strategy), resource support strategy (resource support strategy), institutional strategy (institutional strategy). The data collection is carried out by means of observation, interviews, and documentation to collect the data needed in the form of primary data and secondary data. The number of informants in this study is 3 (three) people. Based on the results of the study, it shows that strategic management in handling drugs at the National Narcotics Agency of Palu City. It has not gone well. From the aspect of organizational strategy (corporate strategy) in this case there is still a lack of socialization carried out by BNNK Palu about the importance of rehabilitation, but organizationally it has carried out counseling by empowering various schools and universities, Program strategies such as conducting counseling have not run optimally due to inadequate budget factors, resource support strategies (resourse support strategy) are already available resources, namely clinics, there are psychologists, doctors, and nurses are in the category of inadequate because they are not permanent employees of BNN, institutional strategies have collaborated between institutions related to the formation of a good school task force as well as community volunteers and students.